(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
the application of immunohistochemistry has opened a new era for examining the age of the wound by forensic specialists, The aim of our study was to illustrate the use of immunohistochemical marker of mast cells activation (mast cell tryptase “MCT”) as a reliable and promising factor of wounds vitality and to Identify the role of pro-inflammatory cytokines: IL 1 beta and IL 6 as parameters of wound age determination. The study was done in the Medico-Legal Directorate of Forensic Medicine (MLD) in Baghdad. The specimens were sera and skin tissues for immunohistochemistry examination, and staining procedures and immunohistochemistry (MCT) ELISA sandwich plate will measure the levels of interleukins. Total autopsy cases were 88 and divided into study group (SG) and control group (CG) .We found that density of Mast cells in sample group was significantly high and higher infiltration that correlates with time passing in the study group as compared by other group in dermis of the sample and control lesions and positive relationship ..dnuow fo ssergorp emit dna level 6?LI & ateb?1 LI fo slevel neewteb